Common Molecular Pathways Between Post-COVID19 Syndrome and Lung Fibrosis: A Scoping Review - Bergantini, Laura; Mainardi, Alessandro; d’Alessandro, Miriana; Cameli, Paolo; Bennett, David; Bargagli, Elena; Sestini, Piersante (Frontiers in Pharmacology, 2022)
ABSTRACT The pathogenetic mechanism of post-Covid-19 pulmonary fibrosis is currently a topic of intense research interest, but still largely unexplored. The aim of this work was to carry out a systematic exploratory search of the literature (Scoping review) to identify and systematize the main pathogenetic mechanisms that are believed to be involved in this phenomenon, in order to highlight the same molecular aspect of the lung. These aims could be essential in the future for therapeutic management. We identified all primary studies involving in post COVID19 syndrome with pulmonary fibrosis as a primary endpoint by performing data searches in various systematic review databases. Two reviewers independently reviewed all abstracts (398) and full text data. The quality of study has been assess through SANRA protocol. A total of 32 studies involving were included,included the possible involvement of inflammatory cytokines,concerned the renin-angiotensin system, the potential role of galectin-3,epithelial injuries in fibrosis, alveolar type 2 involvement, Neutrophil extracellular traps (NETs) and the others implied other specific aspects (relationship with clinical and mechanical factors, epithelial transition mesenchymal, TGF-β signaling pathway, midkine, caspase and macrophages, genetics).. In most cases, these were narrative reviews or letters to the editor, except for 10 articles, which presented original data, albeit sometimes in experimental models.From the development of these researches, progress in the knowledge of the phenomenon and hopefully in its prevention and therapy may originate.